British Art Now : A Subjective View. - Setagaya Art Museum, Tokyo; Fukuoka Art Museum; Nagoya City Art Museum, Nagoya; Tochigi Prefectural Museum of Fine Arts; The Hyogo Prefectural Museum of Modern Art, Kobe; Hiroshima City Museum of Contemporary Art, Hiroshima; Graham-Dixon, Andrew; Meyric-Hughes, Henry; Obigane, Akio; Shioda, Junichi (London : the British Council, 1990)
Campbell, Steven ; Chadwick, Helen ; Cragg, Tony (Anthony) ; Deacon, Richard ; Finlay, Ian Hamilton ; Goldsworthy, Andy ; Gormley, Antony ; Kapoor, Anish ; Brun, Christopher Le ; Mach, David ; Milroy, Lisa ; Rego, Paula ; Tremlett, David ; Webb, Boyd ; Whiteford, Kate ; Wiszniewski, Adrian
British Art Now : A Subjective View, Setagaya Art Museum, Tokyo, 25 August - 7 October 1990 ; Fukuoka Art Museum, 2 November - 25 November 1990 ; Nagoya City Art Museum, 8 December 1990 - 27 January 1991 ; Tochigi Prefectural Museum of Fine Arts, 10 February - 24 March 1991 ; The Hyogo Prefectural Museum of Modern Art, 6 April - 6 May 1991 ; Hiroshima City Museum of Contemporary Art, 18 May - 30 June 1991
biografie, bibliografie
English-Japanese
kunstcatalogus
Keywords: Groot-Brittannië